Faktor-Faktor yang Mempengaruhi Alih Fungsi Lahan Studi Kasus di Subak Daksina, Desa Tibubeneng, Kecamatan Kuta Utara, Kabupaten Badung - DEWA PUTU ARWAN SUPUTRA; I G.A.A AMBARAWATI; I MADE NARKA TENAYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2012)
ABSTRACT The Influencing Factors of Land-use Change: Case Study of Subak Daksina, Tibubeneng Village, North Kuta District, Badung Regency A land-use change of agricultural land into non-farm is increasing every year along with increase in population and development in tourism sector. Accordingly, continuing conversion of agricultural land may lead to food security problem in the future. Determination of factors in affecting agricultural land use shifting was carried out in this study using survey method to farmers. In addition, in-depth interview and observation were used in data collection. Explanatory factor analysis was used to achieve the aims of the study. Results of this study reveals that there were four factors affecting land use shifting, covering land condition, eviction (associated with the human population conditions), land use (for own interests), and the land ineffectiveness. Among 16 variables included in the model, only two variables, i.e. post harvet risk and land tax. Key words: land use, eviction, land ineffectiveness.